Ludwik Wołowski and His Contribution to the French Credit Revolution of the 19th Century - Dobek, Rafał (Studia Historiae Oeconomicae, 2023)
Ludwik Wołowski was a Polish November emigrant in France. There, he gained recognition as an outstanding economist, banker and republican politician. The article focuses on the issue of mortgage loan, which is extremely important for Wołowski. It presents both the theoretical concepts of the Pole from 1834, his political activity in the years 1848–1851 aimed at changing the provisions of the mortgage law in France, and finally the moment of co-creation by Wołowski Crédit Foncier, the first modern mortgage bank in France, and the further history of the bank managed by Wołowski, in the board of which he sat until his death in 1876. In the first part, the text presents not only the criticism of the French mortgage system by Wołowski (primarily the so-called secret mortgages), but also his draft changes and the loan and mortgage model proposed by him and the companies that may grant it. In the second, it shows the parliamentary activity of Wołowski, an attempt to force through appropriate changes in the banking law and the reasons for its defeat. In the third, the most extensive, the article describes not only the very moment of establishing Crédit Foncier and the two-year period of management by Wołowski, but also the further, controversial operation of the bank until the second half of the 1870s. All this against the backdrop of the changing French Monarchy of July, the Second Republic and the Second Empire.